Counterterrorism and Open Source Intelligence - Wiil, Uffe Kock.; SpringerLink (Online service) (Vienna : Springer Vienna, 2011)
Since the 9/11 terrorist attacks in the United States, serious concerns were raised on domestic and international security issues. Consequently, there has been considerable interest recently in technological strategies and resources to counter acts of terrorism. In this context, this book provides a state-of-the-art survey of the most recent advances in the field of counterterrorism and open source intelligence, demonstrating how various existing as well as novel tools and techniques can be applied in combating covert terrorist networks. A particular focus will be on future challenges of open source intelligence and perspectives on how to effectively operate in order to prevent terrorist activities.
Keywords: Computer science; Data protection; Computer Science; Systems and Data Security